2020
DOI: 10.1186/s43055-020-00341-9
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 infection: epidemiological, clinical, and radiological expression among adult population

Abstract: Background High-resolution computed tomography (HRCT) has proved to be an important diagnostic tool throughout the COVID-19 pandemic outbreaks. Increasing number of the infected personnel and shortage of real-time transcriptase polymerase chain reaction (RT-PCR) as well as its lower sensitivity made the CT a backbone in diagnosis, assessment of severity, and follow-up of the cases. Results Two hundred forty patients were evaluated retrospectively for clinical, laboratory, and radiological expression in COVID-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
1
5
1
Order By: Relevance
“…We identified that patients in the severe group had significantly higher levels of laboratory biomarkers (CRP, serum ferritin, and D-dimer) compared to patients in the moderate group. This finding is consistent with that reported in other studies [ 19 , 20 ]. Given that, elevated biomarkers can predict respiratory deterioration; they are currently considered markers of poor outcome for COVID-19 patients and caused by associated systemic hyperinflammatory reactions [ 21 ].…”
Section: Discussionsupporting
confidence: 94%
“…We identified that patients in the severe group had significantly higher levels of laboratory biomarkers (CRP, serum ferritin, and D-dimer) compared to patients in the moderate group. This finding is consistent with that reported in other studies [ 19 , 20 ]. Given that, elevated biomarkers can predict respiratory deterioration; they are currently considered markers of poor outcome for COVID-19 patients and caused by associated systemic hyperinflammatory reactions [ 21 ].…”
Section: Discussionsupporting
confidence: 94%
“…In contrary to our results, Ragab et al[20] reported that crazy paving, septal lines, and lymphadenopathy were more presented in the non-severe cases (87.1%, 81.8 %, 61.1%, respectively). Multivariate regression analysis of the most relevant radiological finding for severity among patients with COVID-19 revealed that GGO with consolidation (OR: 3.52; 95% CI: 1.58-9.63; P = 0.02) and septal thickening (OR: 4.88; 95% CI: (2.13-8.22); P = 0.001) are the most significant finding.…”
contrasting
confidence: 99%
“…At autopsy, it was discovered that the basement membrane of the lung is thicker in diabetic individuals, which may impact pulmonary diffusion function [19]. Furthermore, hypertension patients were more frequently associated with severe COVID-19 pneumonia; it is well recognized that ACE2 is an important regulator of heart activities, which could explain this finding [20]. In this study, significantly low SPO2 and significantly high WBCs, CRP, and ferritin were observed in the severe group.…”
Section: Introductionmentioning
confidence: 51%
“…The main limitation of this study is the retrospective collection of our data which prevented us from further examining the implication of smoking habits (mild/heavy consumption, current/former) and comorbidities on the detected results. Although we cannot ignore a potential cofounding effect for these variables, many cohorts that accounted for comorbidities in their analysis were still able to declare smoking as an independent risk factor that is not affected by specific characteristics of the patients [ 3 , 30 , 31 ]. Taking into consideration these newly emerging reports and our relatively large size cohort, we anticipate that our results will not be highly affected once adjusted for other comorbidities.…”
Section: Discussionmentioning
confidence: 99%